Answer:
44+
Step-by-step explanation:
just got it correct
Answer:
Equation: f(x)=x²-4x+3
Stretch factor: a=1
Step-by-step explanation:
Notice the x-intercepts are (1,0) and (3,0) which can help us determine the equation by setting their expressions equal to 0 and expanding:
(x-1)(x-3)=0
x²-4x+3=0
Therefore, the equation is f(x)=x²-4x+3 where the stretch factor is a=1
is that all of the question?
The answer is D) f(3)= 5
if you look for the y-value when you are on x=3, you get y=5
hope i helped :)
Answer:
its C
Step-by-step explanation:
im smart